Innovative development of small resort towns: the triad of science, business, and education - Ressin, Marat (Frontiers in Sustainable Cities, 2024)
Urban areas are places associated with the transformation of ideas into practices, social initiatives, and spatial economics. The study aims to assess the triad interaction between education, science, and business as a multiplier on the socio-economic development in the region. The study built a conceptual model of socio-economic space in the context of innovative urban development: the unity of education, science, and business. The statistical analysis allowed the author to substantiate the peculiarities of the local triad. The study revealed correlations in the influence of education, science, and business on changes in the regional system. The paper suggests that the triad of education, science, and business rests on territorial specifics. This feature is the determining factor of innovative development in the field of resort towns. The presented research uses the quantitatively measured influence of the triad as a multiplier by combining values of the unity of education, science, and business. The study found that the mentioned indicator reflects the wellbeing and quality of the labor resources in the region. On the one hand, the multiplicative influence of the triad is a guarantee of an increase in the wellbeing level within the borders of the region. On the other hand, it requires adaptation of the innovative development of resort towns to the current growth of the workforce and a decrease in innovative advantages on a local scale. The findings provide policymakers with significant indicators on the way to stabilizing the regional economy and effective decision-making. The study of the interaction between education, science, and business in the context of socioeconomic development can become a crucial tool for formulating policies aimed at stabilizing the region's economy and improving the quality of life of its residents, particularly in resort cities. The obtained results can provide guidelines for the development of innovation support programs and the planning of investment strategies, taking into account the specifics of territorial conditions.